Find cos theta if csc theta = square root 5

Answers

Answer 1
Answer:

Answer:

cos theta = adjacent/hypotenuse = (2)/(√(5) )

Step-by-step explanation:

csc theta = hypotenuse/opposite = √(5) /1 (reciprocal identity)

1^2 + b^2 = √(5)^2 (pythagorean theorem)

b^2 = 5-1

b = 2

cos theta = adjacent/hypotenuse = 2/√(5) (quotient identity)


Related Questions

Rhea has two cardboard boxes in the shape of rectangular prisms. Each box has the same height and cross-sectional area as the other. Which of the following best describes the relationship between the boxes according to Cavalieri's principle?A. The boxes are congruent. B. The surface areas of the boxes are the same. C. The base of each box has the same perimeter as the other. D. The volumes of the boxes are the same.
Find a23 in the sequence -18,-34,-50,-66
jenny`s mom says she has an hour before it's bedtime. Jenny's spends 3\5 of hour texting a friend and 3\8 of the remaining time brushing her teeth and putting on her pajamas. she spends the rest of the time reading her book. how long did jenny read?
Which of the following statement best describes the effect of replacing the graph of f(x) with the graph of f(x) - 3?A) the graph shifts 3 units up. B) The graph shifts 3 units down. i think is correct? C) the graph shifts 3 units left. D)the graph shifts 3 units right.
Need help with: A circle with radius of 9 sits inside a circle with radius of 11 What is the area of the shaded region? Round your final answer to the nearest hundredth.

A student has some​ $1 and​ $5 bills in his wallet. He has a total of 14 bills that are worth ​$38. How many of each type of bill does he​ have?

Answers

They have 6 $5 bills and 8 $1 bills.
There are 7 $1 bills and 8 $5 bills.


Can someone help me fast

Answers

Answer:

(JI)//(LK)

∠JMI opposed by the vertex therefore equal to ∠JMN = (18-2x)°

∠JMN=∠MNK (corresponding angles)(48-2x)°

∠LNH=∠MNK(opposed by the vertex

54-8x=48-2x

-8x+2x=48-54

-6x=-6

x=1

x=1°

Step-by-step explanation:

The sum of 3 consecutive even numbers is 42. The sum can be respresented by n+(n+2)+(n+4)=42. What does n represent?

Answers

Answer:

13

Step-by-step explanation:

n+(n+2)+(n+4)=42

3n+6=42

3n=42-6=36

3n=36

n=13

13+14+15=42

How do i solve each proportion?

Answers

You have to cross multiply (multiply the numerator of the first by the denominator of the second and the numerator of the second by the denominator of the first).

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

[19]

(x+4)/(3) = (4)/(10)

10x+40=12

10x = -28

x=-2.8

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

[21]

(4)/(n+8) = (10)/(8)

32 = 8n + 64

8n = -32

n=-4
19) (x + 4)/(3) = (4)/(10) \n \n x + 4 = (4)/(10) * 3 \n \n x = 1.2 - 4 = -2.8 \n \n x = -2.8 \n \n \n 20) (4)/(n+8) = (10)/(8) \n \n 32 = 8n + 64 \n \n 8n = 32 -64 = -32 \n \n 8n = -32 \n \n n = -4

What is the discriminant of the polynomial 4x^2+4x+1A.) -12
B.) -4
C.) 0
D.) 32

Answers

Answer:

C.) 0

Step-by-step explanation:

ax^2+bx+c

discriminant

b^2 -4ac

4^2-4*4*1

16-16

0

Answer:

\Large \boxed{\mathrm{\bold{C.} \ 0}}

Step-by-step explanation:

The polynomial is given:

4x^2+4x+1

The polynomial is in the form ax² + bx + c.

We can use the discriminant formula:

b^2-4ac

Plugging in the values and evaluating.

4^2-4(4)(1)

16-16

0

The discriminant is 0.

Find f(a), f(a+h) and the difference quotient (f(a+h)-f(a))/ h, where hod want equal 0. F(x)= 2x/ x-1

Answers

First. 

Calculate f'(x) = (2x/x-1)' = (-2)/(x-1)^(2); when x is not 1;

Second.

Calculate f'(0) = -2 => the difference quotient (f(a+h)-f(a))/ h, where hod want equal 0 is -2;

Third.

f(a) = 2a/a-1; f(a+h) = (2a+2h)/(a+h-1);

Answer:

1

Step-by-step explanation: